2019
DOI: 10.21638/spbu03.2019.102
|View full text |Cite
|
Sign up to set email alerts
|

Great Crested Grebe (Podiceps cristatus) synchronies egg laying with protective species

Abstract: Great crested grebes (Podiceps cristatus) are opportunistic breeders nesting in colonies or solitarily in different biotopes with varying nesting dates in different circumstances. On the northern coast of the Neva Bay in the eastern part of the Gulf of Finland, great crested grebes breed solitarily, in colonies situated in reed beds and in a colony on the open water in direct vicinity of a colony of black-headed gulls (Larus ridibundus) and black terns (Chlidonias niger). In the vicinity of the larid colony, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Compared to spring nests, where "colonial" behaviour was detected as the main factor of clutch size, in summer nests the location concerning the edge of littoral vegetation was found to be most important (the distance from shoreline explains 36% of the variability of clutch size). Our result could be in line with the findings of Zaynagutdinova and Mikhailov (2019), who found that pairs nesting on open water started incubation earlier than pairs in reed stands. Later nesting was also found by Bukacinska et al (1993) for non-colonial nesting pairs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Compared to spring nests, where "colonial" behaviour was detected as the main factor of clutch size, in summer nests the location concerning the edge of littoral vegetation was found to be most important (the distance from shoreline explains 36% of the variability of clutch size). Our result could be in line with the findings of Zaynagutdinova and Mikhailov (2019), who found that pairs nesting on open water started incubation earlier than pairs in reed stands. Later nesting was also found by Bukacinska et al (1993) for non-colonial nesting pairs.…”
Section: Discussionsupporting
confidence: 93%
“…This happens mainly through two mechanisms: variable clutch size and asynchronous hatching (Vlug 2005). Changes in reproductive behaviour are also linked with changes in the nesting environment (Marxmeier & Duettmann 2002, Zaynagutdinova & Mikhailov 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation